1990
DOI: 10.1002/ijch.199000032
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Control in Palladium‐catalyzed Allylic Etherification

Abstract: Abstract. Two alternative approaches for increasing the stereospecificity of Pd(0)-catalyzed allylic etherification are presented, both of which also suppress product isomerization and elimination. One of them involves addition of chlorotrimethylsilane to a benzene reaction mixture. In the model reaction studied, it increases the ratio of the two stereoisomeric products, arising from either retention or inversion of configuration at the allylic carbon, from 3:l to 9:1, respectively. The second approach involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…The major concern in carrying out such a test of stereospecificity is the potential for palladium to scramble between the diastereomeric faces of the allyl system …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The major concern in carrying out such a test of stereospecificity is the potential for palladium to scramble between the diastereomeric faces of the allyl system …”
mentioning
confidence: 99%
“…The major concern in carrying out such a test of stereospecificity is the potential for palladium to scramble between the diastereomeric faces of the allyl system. 18 If scrambling were to occur, a mixture of 16 and 17 would be obtained regardless of any stereospecificity in the elimination step. Tsuji's observation that regioisomeric dienes are obtained from the reactions of diastereomeric allylic carbonates in certain rigid polycyclic ring systems 6 suggested that such scrambling is slow relative to elimination with the [Pd(OAc) 2 /PBu 3 ] catalyst system.…”
mentioning
confidence: 99%
“…The same stereochemistry has since been repeatedly observed with organozinc. [30], [32] Similar experiments with organotins pointing to the same conclusion were also reported later by Stille and coworkers. [33], [34] All of these investigations relied on diastereochemical relationships.…”
supporting
confidence: 78%
“…The retention of configuration in the C-C bond-forming step was also confirmed subsequently by the determination of absolute configurations, as shown in Scheme 13. [35] [31] Ph HOOC 90% 94% PhZnCl (2 equiv) Pd(0)L n [30], [32] OAc OAc OAc Ph cat. Pd(PPh 3 ) 4…”
mentioning
confidence: 99%
“…The palladium(0)-catalyzed allylation of nucleophiles (the Tsuji−Trost reaction) is a highly accepted synthetic method due to its broad applicability and facile experimental procedure . The catalytic cycle requires the formation of the cationic π-allylpalladium(II) complex, an intermediate which can be attacked by nucleophiles at the allylic system …”
Section: Introductionmentioning
confidence: 99%